Znaczenie bezpośrednich inwestycji zagranicznych w rozwoju gospodarczym Polski w latach dziewięćdziesiątych - Boratyńska, Katarzyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
In the paper, the importance of foreign direct investment in economic development of Poland in the nineties is presented. The author discussed theories of international capital flows expansion on Poland's example. According to the estimations of P AIZ, the cumulative value of FDI in Poland (since 1993 to June 2002) reached USD 61,6 billion in total. Despite the global downward trend in the FDI movements, in Poland their inflows were worth of USD 3,23 billion in the mid of 2002. Moreover, it was observed growing investors' interest in manufacturing activities in Poland. This in tum is an important factor leading to economic development stimulation and creation of new job places, particularly in the backward regions of Poland. Additionally, the role of FDI in technology improvements in overtaken enterprises as well as their impact on exports and imports were pointed out.